Narrative Construction of Anti-Bullying School Culture through LPKRA Implementation - Anas Rohman; Kholfan Zubair Taqo Sidqi; Erry Nurdianzah; Alex Yusron Al Mufti; Abdul Rozaq; Khalimatus Sadiyah (Yayasan Adra Karima Hubbi, 2026)
Background: Bullying remains a pervasive form of school violence that severely compromises students' psychological, social, and academic development. To mitigate this, educational institutions are increasingly adopting child protection frameworks. A primary initiative in this domain is the Child-Friendly Special Protection Institution (LPKRA) standards, which emphasize policies and pedagogical practices that prioritize the safety and well-being of the child. Purpose: This study aims to delineate the operational model of junior high schools (SMP) that meet LPKRA standards and to analyze the implementation of LPKRA-based anti-bullying education within Semarang City. Method: This research employs a qualitative descriptive approach. Data were gathered through observations, interviews, and documentation involving school principals, teachers, guidance counselors, and students across several junior high schools that have institutionalized LPKRA standards. The data analysis followed the stages of reduction, presentation, and conclusion drawing. Results: The findings indicate that schools adhering to LPKRA standards in Semarang have significantly improved governance by embedding child protection into their core institutional framework. These schools have established formal protection units, enacted anti-violence policies, and developed systematic reporting mechanisms. Anti-bullying education is strategically integrated through school policy, classroom curricula, socialization programs, and active parental involvement. Furthermore, case management utilizes restorative and educational approaches that prioritize the “best interests of the child” principle. Conclusion: The implementation of LPKRA standards effectively fosters a safer, more supportive school environment. While the framework facilitates early detection and resolution of bullying, challenges regarding human resource limitations and program sustainability persist.